2023
DOI: 10.1111/jiec.13380
|View full text |Cite
|
Sign up to set email alerts
|

A review of methods to trace material flows into final products in dynamic material flow analysis: From industry shipments in physical units to monetary input–output tables, Part 1

Abstract: Dynamic material flow analysis (dMFA) is widely used to model stock‐flow dynamics. To appropriately represent material lifetimes, recycling potentials, and service provision, dMFA requires data about the allocation of economy‐wide material consumption to different end‐use products or sectors, that is, the different product stocks, in which material consumption accumulates. Previous estimates of this allocation only cover few years, countries, and product groups. Recently, several new methods for estimating end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 124 publications
0
33
1
Order By: Relevance
“…From these, end-uses can be inferred and assumed according to sector/market label (e.g., "construction"). Industry shipments data often cover only parts of total, economy-wide material consumption (see Streeck et al, 2022). For that reason, many of the studies identified in Streeck et al (2022) do not use industry shipments as direct input to dMFA models.…”
Section: Overview Of the Applied Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…From these, end-uses can be inferred and assumed according to sector/market label (e.g., "construction"). Industry shipments data often cover only parts of total, economy-wide material consumption (see Streeck et al, 2022). For that reason, many of the studies identified in Streeck et al (2022) do not use industry shipments as direct input to dMFA models.…”
Section: Overview Of the Applied Methodsmentioning
confidence: 99%
“…Industry shipments data often cover only parts of total, economy-wide material consumption (see Streeck et al, 2022). For that reason, many of the studies identified in Streeck et al (2022) do not use industry shipments as direct input to dMFA models. Instead, studies calculate end-use shares D by dividing individual by total shipments and apply these shares to total material consumption, as we do here (Equation 1).…”
Section: Overview Of the Applied Methodsmentioning
confidence: 99%
See 3 more Smart Citations